Molecular detection of vector borne pathogens in anemic and thrombocytopenic dogs in southern brazil - Mongruel, Anna Cláudia Baumel; Ikeda, Priscila [UNESP]; de Sousa, Keyla Carstens Marques [UNESP]; Benevenute, Jyan Lucas [UNESP]; Falbo, Margarete Kimie; Machado, Rosangela Zacarias [UNESP]; Carrasco, Adriano de Oliveira Torres; André, Marcos Rogério [UNESP]; Seki, Meire Christina (FapUNIFESP (SciELO), 2018)
Arthropod-borne pathogens are medically important because of their ability to cause diseases in their hosts. The purpose of this study was to detect the occurrence of Ehrlichia spp., piroplasmids and Hepatozoon spp. in dogs with anemia and thrombocytopenia in southern Brazil. EDTA-whole blood was collected from 75 domestic dogs presenting anemia or/and thrombocytopenia from Guarapuava, state of Paraná, Brazil. DNA samples were subjected to conventional PCR assays for Ehrlichia spp. (dsb), piroplasmids (18S rRNA) and Hepatozoon spp. (18S rRNA), followed by sequencing and phylogenetic analyses. Among the 75 dogs, one (1.33%) was positive for Hepatozoon sp. and six (8%) were positive for piroplasmids in 18S rRNA cPCR assays. None of the dogs showed positive results in Ehrlichia spp.-cPCR targeting dsb gene. The phylogenetic analyses revealed that three piroplasm sequences were clustered with Rangellia vitalii, while one sequence was grouped with B. vogeli. The only sequence obtained from Hepatozoon spp.-PCR protocol was pooled with H. canis. Therefore, there is urgent need for differential molecular diagnosis of the two piroplasm species cited as etiological agents in clinical cases of canine hemoparasitic diseases, given the higher pathogenic potential of R. vitalii than of B. vogeli.
Detecção molecular de patógenos transmitidos por vetores em cães anemicos e trombocitopenicos no Sul do Brasil
Keywords: Babesia vogeli; Hepatozoon canis; Phylogenetic analysis; Rangelia vitalii; Tick borne diseases